Synthesis and Characterization of N-Methyl Fatty Hydroxamic Acids from Ketapang Seed Oil Catalyzed by Lipase - Suhendra, Dedy (Molecules, 2019)
N-methyl fatty hydroxamic acid (N-MFHA), which is a derivative of hydroxamic acid (HA), was synthesized from ketapang seed oil (Terminalia catappa L.). In general, HAs have wide applications due to their chelating properties and biological activities. N-MFHAs were synthesized using immobilized lipase (Lipozyme TL IM) in biphasic medium which was the ketapang seed oil dissolved in hexane and N-methylhydroxylamine dissolved in water. The products were characterized through color testing and FT-IR spectroscopy after purification. Various factors affecting the enzyme activity investigated in the study included the effect of incubation time, the amount of lipase used, and the temperature. On the basis of the results, the optimum conditions for the synthesis of N-MFHA obtained are 25 h of incubation time, a temperature of 40 °C, and a ratio of 1:100 for the amount of enzyme (g)/oil (g). At the optimum conditions of the reaction, 59.7% of the oils were converted to N-MFHA.